PERAN PORTER TERHADAP TAMU YANG MENGINAP PADA HOTEL IBIS PEKANBARU - Fadel Muhammad; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to determine how the performance porter at the front office department at the ibis hotel Pekanbaru in Riau.This research uses descrptive quantitative method to study the issues raised. As for the sample in this study as many as 50 people were taken using census sampling. While the data collection techniques in this study using observation, questiuonnaire, and interviews. By using likert scale as a measure to determine the lenght of the short interval.Based on the results of research that has been done, the responsen of the guests to the porter at the hotel ibis Pekanbaru are welcome and greet guests, escort guests into he lobby and to the room, and the latter takes guests who check out to the car. Where the poerter’s role in influencing satisfaction of guests staying at the hotel Ibis Pekanbaru assess that role is still not good porter to guests.Key Words : Role of Porter, Front office department, Ibis Hotel